Time-sliding window and interquartile range (IQR)-based detection of coastal upwelling events in the Southern Java, Indonesia - Herdiyeni, Yeni; Jaya, Indra; Atmadipoera, Agus Saleh; Ahmad, Hafidlotul Fatimah; Lumban-Gaol, Afriel Alex Handro (Frontiers in Marine Science, 2026)
This study proposes a time sliding-window and interquartile range (IQR) based time-series model to detect upwelling events in the Southern Java waters, Indonesia. The methodology encompasses data acquisition, pre-processing, seasonal analysis, upwelling detection, measurement of upwelling intensity, and lag time assessment. The results show significant seasonal variations in sea surface temperature (SST) and chlorophyll-a concentrations, with pronounced SST decreases between May and September, indicating active upwelling during this period. Spatial analysis identifies high-intensity upwelling centers concentrated between 105°E–120°E longitude and 7.5°S–9.5°S latitude, with prominent clusters around 110°E–115°E. Lag time analysis indicates shorter biological response times in upwelling centers during boreal spring and summer, with a median of 7 days and a mean of 4.2 days, respectively, reflecting a rapid onset of upwelling conditions in these seasons. These findings provide insights that may support the optimization of fishing operation by identifying periods and locations with enhanced marine productivity. Additionally, understanding upwelling dynamics also supports sustainable fisheries management, as nutrient-rich zones provide continuous food supply for marine organism to reproduction and growth. This research presents a quantitative framework for detecting and characterizing upwelling intensity, contributing to improved monitoring and management of coastal marine resources.